2021
DOI: 10.3389/fsoc.2021.741971
|View full text |Cite
|
Sign up to set email alerts
|

Trust, Sociability, and Quality of Life of Sub-Saharan African Migrants in Germany

Abstract: Poor social integration is associated with poor quality of life among minority groups. The current study hypothesized that trust and sociability may significantly explain the quality of life performance among Sub-Saharan African migrants in Germany. Data from 518 migrants were analyzed. Hierarchical multiple linear regression models were calculated to assess the predictive effect of trust and sociability on aggregate quality of life. Results show that general trust and sociability explained about 21% of the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…In the adjusted linear regression model, several sociodemographic variables were predictors of the QoL. Length of stay was negatively associated with the perception of overall general health, which is consistent with the previous study on the migrant population [ 63 ]. Regarding the physical health domain of QoL, higher age was a significant predictor of lower physical health, which is in line with the previous research [ 64 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the adjusted linear regression model, several sociodemographic variables were predictors of the QoL. Length of stay was negatively associated with the perception of overall general health, which is consistent with the previous study on the migrant population [ 63 ]. Regarding the physical health domain of QoL, higher age was a significant predictor of lower physical health, which is in line with the previous research [ 64 ].…”
Section: Discussionsupporting
confidence: 88%
“…Social Integration: This measure underpins various concepts to assess behavioral patterns based on the need for individuals to integrate into communities to facilitate personal growth and improve quality of life [ 29 , 62 ]. These scales are important to describe relationships related to financial support, belonging, and friendship.…”
Section: Methodsmentioning
confidence: 99%
“…Various socio-demographic characteristics assessed as control variables were sex (male and female), age (20–25, 26–30, 31–35, 36–40, and >40), and education (none, primary, secondary and tertiary) and marital status (married, single, widowed, and divorced) were also explored. Socio-demographic variables were controlled for because several studies have indicated that these factors influence the formation of social networks [ 28 , 29 , 69 ]. By controlling for these socio-demographic variables, all forms of bias resulting from the different characteristics of the recruited displaced persons are controlled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QoL addresses the subjective evaluation of individuals' interpretation of life outcomes regarding their immediate environment's culture, goals, expectations, standards, and value systems [28]. Several studies have examined the QoL of international students [29,30], while a few have faintly focused on SSA students as part of a more extensive study [2,31,32]. None specifically studied SSA students as a wholesome group.…”
Section: Introductionmentioning
confidence: 99%